Non-invasive prenatal detection of trisomy 21 by quantifying segmental duplication in maternal plasma with digital PCR. Issue 10 (18th February 2016) - Xu, Shu; Zou, Bingjie; Xiang, Zheng; Miao, Mingzhu; Song, Qinxin; Huang, Huan; Wu, Haiping; Zhou, Guohua
Abstract : We proposed a novel method for the detection of trisomy 21 by quantifying the slightly increased amount of chromosome 21 in cfDNA. Abstract : Non-invasive detection of trisomy 21 is a safe and effective way for prenatal diagnosis. Although using next generation sequencing technology can achieve non-invasive detection of chromosomal abnormalities, a more convenient and cost-effective method is preferable for routine clinical applications. Here, we proposed a novel method for the detection of trisomy 21 by accurately quantifying the slightly increased amount of chromosome 21 in cell-free DNA from maternal plasma using digital PCR. The segmental duplication fragments on chromosome 21 and chromosome 1 were employed as the detection target of digital PCR. As low as 10% cell-free fetal DNA of trisomy 21 fetus in maternal cell-free DNA was successfully detected. Three trisomy 21 samples were unambiguously picked up from 15 clinical samples, indicating that our method has the potential for non-invasive diagnosis of trisomy 21.